2012
DOI: 10.18097/pbmc20125802131
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides: mode of action and perspectives of practical application

Abstract: 1Московская государственная академия тонкой химической технологии им. М.В. Ломоносова 119571, Москва, пр-т Вернадского, 86; тел.: 8-495-936-89-03; эл. почта: laboratory211@yandex.ru 2 ООО "Фарминтерпрайсез", МоскваОбзор посвящен антимикробным пептидам (АМП), обладающим антибактериальной, противовирусной и антигрибковой активностью. Рассмотрены структура и механизмы действия АМП на липидную мембрану и внутриклеточные мишени патогенов. Проанализировано современное состояние и перспективы практического применения… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…There is some optimism that these obstacles may soon be overcome by new strategies that combine natural cationic peptides and stable synthetic immunomodulatory peptides [ 29 ]. In this regard, peptide drugs such as Polymyxin B and gramicidin that are used for the treatment of Gram-negative bacterial infections are reported to be safe and effective, and peptides such as the indolicidin-derived CLS001 (previously known as MX594AN) have reached phase III clinical trials with promising prospects [ 62 64 ]. Because of their evolutionary distance, during which their survival against microbes has been solely dependent on innate immunity, insects provide interesting models for novel AMP drug design [ 65 , 66 ].…”
Section: Antimicrobial Peptides In Clinical Medicinementioning
confidence: 99%
“…There is some optimism that these obstacles may soon be overcome by new strategies that combine natural cationic peptides and stable synthetic immunomodulatory peptides [ 29 ]. In this regard, peptide drugs such as Polymyxin B and gramicidin that are used for the treatment of Gram-negative bacterial infections are reported to be safe and effective, and peptides such as the indolicidin-derived CLS001 (previously known as MX594AN) have reached phase III clinical trials with promising prospects [ 62 64 ]. Because of their evolutionary distance, during which their survival against microbes has been solely dependent on innate immunity, insects provide interesting models for novel AMP drug design [ 65 , 66 ].…”
Section: Antimicrobial Peptides In Clinical Medicinementioning
confidence: 99%
“…Antimicrobial peptides (AMPs) have multiple targets on pathogenic microbes, including the cytoplasmic membrane and cell division and synthesis of essential proteins (Okorochenkov et al, 2012). One drawback of AMPs is their limited antimicrobial spectrum, susceptibility toward proteolytic degradation, and moderate antimicrobial activity (Habets and Brockhurst, 2012; Frontiers in Microbiology | www.frontiersin.org 2 June 2021 | Volume 12 | Article 624465 Niu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Second, AMPs can exert inhibitory effects (Marchand et al, ). Most AMPs exhibit rapid killing of microbes (Okorochenkov, Zheltukhina, & Nebol’Sin, ), and some have a strong killing effect on cancer cells (Piktel et al, ; Wu et al, ). Tissue specificity studies revealed that in fish, AMPs are expressed in all examined tissues.…”
Section: Introductionmentioning
confidence: 99%